The Impact of Digital Waste Initiatives on Enhancing Community Mindset in Daleman Kidul Village Aiming to Boost the Village Economy Through Maggot Farming, Organic Fertilizer Production, and Crafts from Inorganic Waste. - Faris Candra Priyana; Muhammad Faiz Rachmadianto; Ahmad Rif’an; Budi Hartono (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to analyze the impact of the Digital Waste House (DWH) program on improving the economy and changing the mindset of the people of Daleman Kidul Village, Pakis Subdistrict, Magelang Regency. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and literature studies. The results showed that the DWH program positively impacted the economy and community mindset. This program increases awareness and community participation in waste management and opens opportunities to increase residents' income through selling waste sorting results, cultivating maggots, processing organic fertilizers, and making handicrafts from inorganic waste.